Diseño y construcción de un equipo automatizado para el estudio del drenaje de líquidos en un tanque cilíndrico vertical - Cosi Sucaticona, Carlos Daniel (2024)
The general objective of the present investigation was: to be designed for and to construct an equipment automated for the study of the liquids drainage in a cylindrical vertical tank, of which were its main components: a cylindrical vertical tank of 0.5 m of diameter and 0.7 m of height, a viewfinder with gauged rule, a PLC, an electric valve, an interface of communication and a thermic key. In order to deduct the equation between the passage of time from initial and final functioning of the electroválvula with the heights of liquid in the aforementioned tank, was applicable the equations of balance of mass, of continuity and of conservation of energy. The values of the initial height of the liquid along with the ones of the draining volume, in the eight realized proofs were: (53 cm, 20 L); (42.5 cm, 18 L); (33 cm, 15 L); (25.4 cm, 20 L); (54.8 cm, 20 L); (44 cm, 18 L); (34.5 cm, 15 L) and (27 cm, 16.5 L); proving to be the passage of time of functioning of the electric valve along with the percentage of error of the draining volume: (179.1 s, 3.08 %); (176.6 s, 3.63 %); (162.1 s, 0.52 %); (244.5 s, 4.77 %); (176.5 s, 4.07 %); (174.5 s, 3.63 %); (159.2 s, 1.83 %) and (194.1 s, 4.8 %); being proved in this way that the deduced equation has a bigger reliability of the 95 %; which indicated that the general objective was caught up with and in turn it tried on its general hypothesis.